Repurposing small molecules of Tephrosia purpurea against SARS-CoV-2 main protease - Sahoo, Rosaleen; Sahu, Parameswar; Swargam, Sandeep; Kumari, Indu; Behera, Banshidhar (Journal of Biomolecular Structure and Dynamics, 2023)
Coronavirus infection is a communicable disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which emerged as a global pandemic with deteriorating effect on the world's population. Main protease (M-pro) of SARS-CoV-2 plays a significant role in the viral replication, transcription and disease propagation as well as a potential candidate for drug discovery and development for COVID-19 infection. The current study employed state of art structure-based drug discovery to decipher the role of phytochemicals of Tephrosia purpurea against M-pro. Tephrosia purpurea is being used as a traditional medicinal plant for the treatment of cough, breathlessness and fever as per the Indian Materia Medica. Screening of the phytochemicals of Tephrosia purpurea against M-pro was performed using molecular docking approach to identify the top 5 hits (+)-tephrorin B, deguelin, vitamin p, lanceolarin and 3beta-hydroxy-20(29)-lupene with binding energy of -8.4, -8.1, -8.0, -7.8, and -7.8 kcal/mol, respectively. Furthermore, identified top 5 hits were subjected to drug-likeness and toxicity prediction as well as MM-GBSA calculation. Out of the five molecules four molecules were predicted not to comprise any mutagenic and carcinogenic effects. Top two molecules based on the drug-likeness properties for oral bio-availability were further analysed by molecular dynamics simulation at 100 ns timescale. It was observed from the dynamic behaviour of the two complexes that the addition of these molecules changed the conformation and stability of the apo protein; thus may act as inhibitors for M-pro. Communicated by Ramaswamy H. Sarma
Keywords: molecular dynamics; SARS-CoV-2; Tephrosia purpurea

Repurposing phytochemicals of Citrullus colocynthis against maltase-glucoamylase using molecular docking, MMGBSA, MD simulation and linear regression to identify potential anti-diabetic compounds - Sahu, Parameswar; Sahoo, Rosaleen; Sahu, Abhishek Kumar; Saluja, Sundeep Singh; Behera, Banshidhar (Journal of biomolecular structure and dynamics, 2024)
Diabetes is a common lifestyle disorder found in populations of different age groups. Maltase-glucoamylase catalyses the release of the glucose molecule in the final enzymatic reaction of starch digestion; therefore, inhibition of maltase-glucoamylase is one of the approaches in the development of therapeutics for diabetes. Citrullus colocynthis is commonly recommended in Ayurveda for the treatment of diabetes. The current study applied a structure-based drug design approach to repurpose the phytochemicals of Citrullus colocynthis to identify potential inhibitors for maltase-glucoamylase. 70 phytochemicals of Citrullus colocynthis were screened against maltase-glucoamylase and top 5 molecules 8-p-hydroxybenzylisovitexin, isoorientin, cucurbitacin B, cucurbitacin E, and cucurbitacin I with significant binding energy of -10 kcal/mol, -9.9 kcal/mol, -9.6 kcal/mol, -9.2 kcal/mol, and -7.7 kcal/mol were identified. Furthermore, MMGBSA, pharmacokinetics properties and toxicity prediction were performed on the five identified molecules and top 3 molecules were selected for molecular dynamics (MD) simulation. It was observed from the structural flexibility and dynamic behaviour of the systems that conformational changes were noticed in the complexes as compared to its native state, which suggests that the 3 molecules, namely 8-p-hydroxybenzylisovitexin, isoorientin, and cucurbitacin I of Citrullus colocynthis may act as inhibitors for maltase-glucoamylase.Communicated by Ramaswamy H. Sarma
Keywords: Citrullus colocynthis; Diabetes; linear regression; molecular dynamics simulation; phytochemicals